Miniaturized Inset-Fed Microstrip Patch Sensor Based on Meander-Line Slot for Water Measurement Applications - Aya Khalid Hadi; Mahmood Farhan Mosleh; Raed A. Abd-Alhameed (Journal of Techniques)
This article introduces a high-sensitive microstrip-patch sensor-based meander-line slot structure for water measurement applications. The HFSS software tool is employed to design and simulate the proposed system. The inset-fed sensor size is 60×50×1 mm3 and is printed on a low-cost FR-4 dielectric substrate. The meander-line slots resonator is used in the proposed design to produce strong and concentrated electric fields while increasing the energy output by focusing the current in a narrow area. In addition to enhancing sensitivity, it decreases the sensor dimension, provides a region with strong electric fields, and increases the interaction area with the water. This sample needs to be tested. For the unloaded condition, the miniaturized sensor is resonant at 2.863 GHz with a reflection coefficient (S11) amplitude equal to -30.219 dB. At the same time, the miniaturized sensor is deep at 2.144 GHz, 2.148 GHz, and 3.14 GHz for DI-water, freshwater, and seawater-loaded conditions. According to simulated results, high sensitivity values are found. The sensor has sensitivities of 3.14 and 1.21 for DI water and seawater, respectively. The high sensitivity values of the proposed sensor indicate that any slight change in the εr around the sensing area of the proposed sensor will be translated into significant changes in the resonant frequency and the recorded output results.